Sleepiness and Clinical Readiness in Prelicensure Undergraduate Nursing Students - Rhonda Winegar; Katherine Kreis; Michael Holmes; Jennifer Roye; Narayanan Janakiraman; Zhaoli Liu (Nurse Educator, 2026)
Background: Sleep deprivation is common among undergraduate nursing students and may affect cognitive processing and clinical decision-making. While clinician fatigue is well studied, less is known about how student sleepiness relates to foundational skills performance. Purpose: This study examined associations between self-reported sleepiness and clinical readiness during standardized skills checkoffs. Methods: In a cross-sectional sample of 83 students, participants completed the Karolinska Sleepiness Scale (KSS), Pittsburgh Sleep Quality Index, and 6 faculty-graded skills evaluations. Mann–Whitney U tests and logistic regression assessed relationships between sleep variables and pass/fail outcomes. Results: Higher Pittsburgh Sleep Quality Index scores corresponded with higher KSS values, and some skills showed more failures at higher sleepiness levels. Only medication administration differed significantly by KSS group ( U = 338, P = .016). Other skills and the logistic model were nonsignificant. Conclusion: Descriptive trends suggested possible links between sleepiness and performance, but inferential results were inconsistent.